Resposta imune humoral específica ao mosquito Aedes aegypti em crianças com prurigo estrófulo - Aires, Roberto Tschoepke (2021)
Background: Prurigo Strophulus (PS) is a chronic dermatosis resulting from hypersensitivity reaction to insect bites, whose diagnosis is clinical and based on the appearance and distribution of the lesions. Despite being common in our environment, PS is little studied and the immunopathological mechanism is not exactly known. Objective: To determine the clinical and demographic characteristics of patients with PS and the profile of specific immunoglobulins against mosquito antigens. Methods: An analytical cross-sectional observational study in which children under 14 years of age, with a clinical diagnosis of PS, were evaluated. Clinical and sociodemographic data were collected, as well as blood samples that were submitted to the ELISA test to measure specific antibodies against Aedes aegypti salivary gland antigens, mosquito body antigens and antigens from a commercial extract containing Aedes and Culex sp total body. A severity score (not validated) was developed by the researchers and involved 4 criteria: manifestation of allergic disease (report of asthma, rhinitis or atopic dermatitis), affected body region(s), use of antibiotics to treat skin infections secondary to PS and intensity of pruritus. Results: Of the 107 children evaluated, 64 (59.8%) were male and 47 (43.9%) were under 5 years old. Most 83 (77.6%) lived in urban/suburban regions and 98.1% reported the presence of mosquitoes in their homes. Seventy-four children (69.1%) started symptoms at less than 2 years of age and 47 (43.9%) reported worsening in the summer. The lower limbs were affected in 100% of the children and the papule was the most frequent elementary lesion, present in 59 (55.2%) patients. The manifestation of allergic disease (asthma and/or rhinitis and/or atopic dermatitis) was present in 83 (77.6%) patients. Regarding the severity score, 63 (58.9%) had a score greater than 11, considered serious by the researchers. Correlating clinical history variables with the severity score, we observed a significant relationship between children who started symptoms before 2 years of age and a higher severity score (p=0.0326). Based on the similarity of recognition profile of antibodies specific to the A. aegypti gland antigens generated by the heat map, we divided the patients into 3 groups (clusters). The signature generated by cluster 3 was associated with a higher PE severity (median=12.50; IQR=11.0 and 15.0) compared to cluster 2 (median=9.0; IQR=4.5 and 13 .5; p<0.05). We observed in Cluster 3 higher AgGlan-specific IgG4 and IgG reactivity. Discussion: This is the first study in Brazil to investigate the clinical characteristics and profile of specific immunoglobulins against mosquito antigens from children with PS. The confirmation of specific antibodies against mosquitoes by laboratory methods plays na important role in identifying sensitization to these allergens and, when interpreted in conjunction with the clinical history, suggests a probable immunological mechanism of the disease. Conclusion: Greater severity is observed in children under 2 years of age. Among the investigated immunoglobulins, IgG4 seems to be related to the severity of the disease. Additional studies are needed to validate PE severity score and to confirm the participation of IgG4 in the pathophysiological mechanism.